Exploring GeoGebra acceptance: an implication for pre-service mathematics teachers’ professional development - Ebenezer Kwesi Lotey; Francis Ohene Boateng; Yarhands Dissou Arthur; Benjamin Adu-Obeng; Joseph Frank Gordon (Cogent Education)
21st-century graduates are gradually tagged to be technologically literate to solve challenging problems. Graduates’ skills in problem-solving, critical thinking, and collaboration are needed in solving these challenges. Educational technology like GeoGebra integration greatly nurtures and shapes such skills. Per this, mathematics student facilitators’ at Akenten Appiah-Menka University of Skill Training and Entrepreneurial Development (AAMUSTED) are educated on how to use GeoGebra in learning and improving students’ competence in using GeoGebra for future teaching. This study focused on pre-service mathematics facilitators and the application of TAM in relation to post-training technology acceptance to understand the factors that affect GeoGebra adoption. A quantitative design based on a purposive and convenience sampling approach was utilised to gather 201 valid data from students. The path estimation for the theorised hypotheses was determined from Structural Equation Modeling utilising AMOS v.23. The study found that GeoGebra easiness positively predicted GeoGebra usefulness and GeoGebra attitudinal. The impact of GeoGebra usefulness was positively influence both GeoGebra attitudinal and GeoGebra intention. Students’ attitudes significantly predicted students’ intentions. The findings suggest that expanding mathematical technology training in tertiary institutions can maximise the acceptance and utilisation of technology like GeoGebra, contributing to the broader goal of enhancing digital literacy in education.